Campur Kode dalam Dialog Film Agak Laen: Cerminan Dinamika Identitas dan Hibriditas Budaya di Era Global: Code-Mixing in the Dialogue of the Film Agak Laen: Reflecting the Dynamics of Identity and Cultural Hybridity in the Global Era - Intan Mastura (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Code-mixing is a form of language variation that commonly occurs in bilingual and multilingual societies, including Indonesia. Films, as representations of social life, often depict code-mixing in character dialogues, reflecting the linguistic dynamics of society. This study aims to (1) describe the forms and types of code-mixing found in the speech of the characters in the film Agak Laen and (2) identify the social dynamics, identity, and language culture represented in the film. This study uses a qualitative descriptive approach with a sociolinguistic perspective. Data were collected through listening and note-taking for the film's dialogues, then analyzed using code-mixing theory, specifically the classification of inner and outer code mixing. The analysis was carried out by linking the forms of code-mixing to their social contexts and communicative functions. The results show that code-mixing appears in various forms with diverse functions, including as a strategy to build humor, emphasize character, display social identity, and create closeness in interactions. In addition, code-mixing reflects the influence of globalization and shifts in language culture in contemporary Indonesian society. Thus, this study contributes to sociolinguistic studies by showing that code-mixing practices in films are not only aesthetic but also represent dynamic social and linguistic realities.